2014
DOI: 10.1167/14.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Follow the leader: Visual control of speed in pedestrian following

Abstract: When people walk together in groups or crowds they must coordinate their walking speed and direction with their neighbors. This paper investigates how a pedestrian visually controls speed when following a leader on a straight path (one-dimensional following). To model the behavioral dynamics of following, participants in Experiment 1 walked behind a confederate who randomly increased or decreased his walking speed. The data were used to test six models of speed control that used the leader's speed, distance, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 53 publications
7
65
0
Order By: Relevance
“…The understanding of collective behavior has been advanced tremendously by theoretical models and largescale simulations, but there is a growing consensus that this effort must be informed by rigorous observational and experimental studies to specify the local rules or control laws that give rise to global phenomena. Driven in part by recent advances in tracking technologies, there is a rising tide of data-driven approaches to collective behavior, including work on fish schools (Ward et al (2008)), bird flocks (Ballerini et al (2008); Cavagna et al (2010)), as well as pedestrian behavior (Moussaid et al (2009) ;Lemercier et al (2012); Rio et al (2014)) and crowd dynamics (Moussaid et al (2010); Bonneaud et al (2012)) in humans. Data can be utilized in many ways, from calibrating the parameters of proposed models (Johansson et al (2007)) to identifying the information individual agents utilize to guide behavior (Ballerini, et al (2008)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The understanding of collective behavior has been advanced tremendously by theoretical models and largescale simulations, but there is a growing consensus that this effort must be informed by rigorous observational and experimental studies to specify the local rules or control laws that give rise to global phenomena. Driven in part by recent advances in tracking technologies, there is a rising tide of data-driven approaches to collective behavior, including work on fish schools (Ward et al (2008)), bird flocks (Ballerini et al (2008); Cavagna et al (2010)), as well as pedestrian behavior (Moussaid et al (2009) ;Lemercier et al (2012); Rio et al (2014)) and crowd dynamics (Moussaid et al (2010); Bonneaud et al (2012)) in humans. Data can be utilized in many ways, from calibrating the parameters of proposed models (Johansson et al (2007)) to identifying the information individual agents utilize to guide behavior (Ballerini, et al (2008)).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have advocated for an experimental approach to collective behavior that begins by developing dynamical models of simple pedestrian inte and Warren (2003) and Warren (2007); Rio et al (2014)), extends them to more complex scenarios (Kiefer et al (2013)), and ultimately uses them to predict patterns of crowd dynamics (Bonneaud et al (2014)). We recently showed that a pedestrian follows a neighbor by matching the leader's speed and heading direction, based on visual information ; Dachner and Warren (2014)).…”
Section: Introductionmentioning
confidence: 99%
“…A useful illustration of these concepts is found in a study on inter personal leader-follower coordination during locomotion. Rio et al (2014) demonstrated that following speed is likely controlled by a simple control law: Followers matched leader walking speed by minimizing the change in optical angle subtended by the leader at the follower's eye. This model was accurate even with random changes in leader speed.…”
mentioning
confidence: 99%
“…Specifically, spatial movement and social interactions play an important role in the context of pedestrian dynamics. Perceptual motor-control models can be used to describe individual steering behaviour, including collision avoidance [5][6][7]. Social interactions have been successfully studied with individual-based simulation models [8,9], which typically have a set of behavioural rules or equations of motion and are studied by varying the model's parameters to explore differences in behaviour.…”
Section: Introductionmentioning
confidence: 99%